The identification and characterisation of carbonaceous interface layers of graphene using polarisation-dependent X-ray reflectometry. (October 2018) - Wahab, H.; Jansing, C.; Mertins, H.-Ch; Kim, J.H.; Choi, S.-H.; Gaupp, A.; Timmers, H.
Abstract: The complex refractive index has been determined for graphene for linearly polarised light in p- and s-geometry at energies across the carbon 1s edge. The imaginary part was measured with absorption spectroscopy. The real part was derived using Kramers-Kronig transformations. Results have been validated by X-ray reflectometry of substrate-supported graphene. Theoretical modelling demonstrates that reflection spectra are strongly affected by the relative difference between the reflectance of graphene and its substrate. Measured reflection spectra show that graphene is often sandwiched between a carbonaceous layer of surface-adsorbates and another carbonaceous layer between graphene and substrate. Reflectometry distinguishes adventitious layers from the graphene because of a different energy-dependence of the refractive index. The carbonaceous interface layers can be modelled well with the refractive index function measured for an adventitious surface layer on silicon. The carbon observed at the substrate-interface may originate from the transfer of a graphene sheet from a deposition-substrate. The optically-effective thickness and anisotropy of adventitious carbonaceous layers can be extracted from reflectance spectra. The bonds of adventitious carbon tend to be normal to the basal plane of graphene. Transferred graphene typically has a substrate-interface three times its own thickness and is covered by one layer of surface adsorbates. Graphical abstract: Image 1